Discontinuous Mayer control problem under state-constraints - Plaskacz, Sławomir; Quincampoix, Marc (Topological Methods in Nonlinear Analysis, 2000)
This paper deals with Mayer's problem for control systems withstate constraints and, possibly, discontinuous terminal cost.The main result of this paper consists in the characterization ofthe value function as the unique solution to an Hamilton-Jacobiequation. The above characterization extends results alreadyobtained in the case of regular cost functions and under somecontrolability assumptions on the boundary of the set ofconstraints.